UPAYA MENINGKATKAN KETERAMPILAN 4C (CRITICAL THINKING, COLLABORATIVE, COMMUNICATIVE, DAN CREATIVE) MELALUI PROJECT BASED LEARNING - Putri, Neuwidia Nuzul; Ningsih, Kurnia; Supartini, Sri (Universitas Islam Negeri Ar-Raniry, 2023)
Softskills in the form of 4C skills (critical thinking, creativity, communication, and collaborative) need to be equipped to students through strategies that can be used by educational institutions. The purpose of this study was to improve students' 4C skills by applying the Project Based Learning (PjBL) model. This type of research is Classroom Action Research (PTK). The classroom action research procedure was carried out with two cycles with two meetings in each cycle. This study used instruments in the form of observation sheets and written evaluation tests. Data collection techniques in this study include (1) observation, (2) tests, and (3) documentation. The results showed an increase in 4C skills through Project Based Learning (PjBL). Critical thinking skills at the end of cycle II increased by about 46.7% from 33.3% to 80%. Collaborative skills at the end of cycle II increased by about 20% from 66.7% to 86.7%. Communication skills at the end of cycle II increased by about 26.7% from 53.3% to 80%. Creative thinking skills at the end of cycle II increased by 40% from 46.7% to 86.7%. It is concluded that this research proves that 4C skills (critical thinking, collaborative, communicative, and creative) can be improved effectively by applying the Project Based Learning (PjBL) model.